Unleashing Central America’s Growth Potential : Guatemala - Ulku, Hulya (World Bank, Washington, DC, 2021)
The objective of this study is to investigate the drivers and constraints of growth and productivity in Guatemala and explore areas with high growth potential. Drawing on the historical growth experience of Guatemala and employing a range of analytical tools, this country analysis aims to provide an in-depth study of the drivers and constraints of the country’s economic growth. The report first takes stock of the historical growth and macro performance of the country, before moving to a growth accounting exercise to understand the past drivers of the country’s growth. In the same vein, the subsequent section analyzes aggregate trends in productivity, the engine of long-term growth, and its relation to the process of structural transformation. The study then uses a cross-country benchmarking and panel data regression analysis based on the growth diagnostic developed by Hausmann et al. (2005) to identify the binding constraints to growth. Finally, the analysis presents the links between growth, diversification, and exports. This analysis relies on a wide range of analytical tools, which are applied to each of the six countries in the study to enable cross-country comparisons. Several quantitative methods are employed to provide an objective assessment of the drivers and constraints of growth in Guatemala, including the long-term growth model (LTGM), the computable general equilibrium model (CGE), growth diagnostics, and product space analyses. This same framework, analytical tools, and data are used for each Central American country to conduct a parallel analysis that enables meaningful cross-country comparisons. Therefore, given the wide breadth of the study, in terms of the methodologies used, subjects analyzed, and countries covered, it does not aim to analyze in depth each driver and constraint of growth and provide granular policy recommendations. The core objective of this study is to inform the policy makers and other interested parties about the country’s strengths and weaknesses related to its growth, and to establish the analytical basis for subsequent investigations of specific areas.